Unconventional myosins acting unconventionally - Woolner, Sarah (Trends Cell Biol, 2009)
Unconventional myosins are proteins that bind actin filaments in an ATP-regulated manner. Because of their association with membranes, they have traditionally been viewed as motors that function primarily to transport membranous organelles along actin filaments. Recently, however, a wealth of roles for myosins that are not obviously related to organelle transport have been uncovered, including organization of F-actin, mitotic spindle regulation and gene transcription. Furthermore, it has also become apparent that the motor domains of different myosins vary strikingly in their biophysical attributes. We suggest that the assumption that most unconventional myosins function primarily as organelle transporters might be misguided.